Interactions Between 2D Materials and Living Matter: A Review on Graphene and Hexagonal Boron Nitride Coatings - Santos, João; Moschetta, Matteo; Rodrigues, João; Alpuim, Pedro; Capasso, Andrea (Frontiers in Bioengineering and Biotechnology, 2021)
Two-dimensional material (2DM) coatings exhibit complex and controversial interactions with biological matter, having shown in different contexts to induce bacterial cell death and contribute to mammalian cell growth and proliferation in vitro and tissue differentiation in vivo. Although several reports seem to indicate that the morphologic and electronic properties of the coating, as well as its surface features (e.g., crystallinity, wettability, and chemistry) play a key role in the biological interaction, these kinds of interactions have not been fully understood yet. In this review, we report and classify the cellular interaction mechanisms observed in graphene and hexagonal boron nitride (hBN) coatings. Graphene and hBN were chosen as study materials to gauge the effect of two atomic-thick coatings with analogous lattice structure yet dissimilar electrical properties upon contact with living matter, allowing to discern among the observed effects and link them to specific material properties. In our analysis, we also considered the influence of crystallinity and surface roughness, detailing the mechanisms of interaction making specific coatings of these 2DMs either hostile towards bacterial cells or innocuous for mammalian cells. In doing this, we discriminate among the material and surface properties, which are often strictly connected to the 2DM production technique, as well as the coating deposition and post-processing methods. Building on this knowledge, the selection of 2DM coatings based on their specific characteristics will allow to engineer desired functionalities and devices. Antibacterial coatings to prevent biofouling, biocompatible platforms suitable for biomedical applications (e.g., wound healing, tissue repairing and regeneration, and novel biosensing devices) could be provided soon. Overall, a clear understanding on how the 2DM coating’s properties may modulate a specific bacterial or cellular response is crucial for any future innovation in the field.